Self-Eating on Demand: Autophagy in Cancer and Cancer Therapy - Jon D. Lane (Frontiers Research Topics, 2018)
Macroautophagy, the major lysosomal pathway for recycling intracellular components including whole organelles, has emerged as a key process modulating tumorigenesis, tumor-stroma interactions, and cancer therapy. An impressive number of studies over the past decade have unraveled the plastic role of autophagy during tumor development and dissemination. The discoveries that autophagy may either support or repress neoplastic growth and contextually favor or weaken resistance and impact antitumor immunity have spurred efforts from many laboratories trying to conceptualize the complex role of autophagy in cancer using cellular and preclinical models. This complexity is further accentuated by recent findings highlighting that various autophagy-related genes have roles beyond this catabolic mechanism and interface with oncogenic pathways, other trafficking and degradation mechanisms and the cell death machinery. From a therapeutic perspective, knowledge of how autophagy modulates the tumor microenvironment is crucial to devise autophagy-targeting strategies using smart combination of drugs or anticancer modalities. This eBook contains a collection of reviews by autophagy researchers and provides a background to the state-of-the-art in the field of autophagy in cancer, focusing on various aspects of autophagy regulation ranging from its molecular components to its cell autonomous role, e.g. in cell division and oncogenesis, miRNAs regulation, cross-talk with cell death pathways as well as cell non-autonomous role, e.g. in secretion, interface with tumor stroma and clinical prospects of autophagy-based biomarkers and autophagy modulators in anticancer therapy. This eBook is part of the TransAutophagy initiative to better understand the clinical implications of autophagy in cancer.